[PP.25.21] STRIKING EFFICACY OF TRANSCUTANEOUS ELECTRICAL NERVE STIMULATIONS IN PERIPHERAL POLYNEUROPATHIES IN DIABETES MELLITUS II-I, CKD IV-V AND PRIMARY HYPERTENSION. (September 2016) - Gokçay, I.; Sagliker, Y.; Kozanoglu, E.; Kelle, B.; Paylar, N.; Ozkaynak, P. Sagliker; Sagliker, H.S.
Abstract : Objective: The polyneuropathies associated with diabetes mellitus type II-I, chronic kidney disease IV-V and primary hypertensives are referred by long term complications. Especially, painfull polyneuropathy situations decrease the quality of the patient's lifes severely. Transcutaneous Electrical Nerve Stimulation (TENS) is a method which is used in painfull polyneuropathy treatment. In our study, we tried to evaulate the analgesic efficiency of Transcutaneous Electrical Nerve Stimulation (TENS) in diabetics II-I, CKD IV-V and primary hypertensives. And also polyneuropathy patients' life quality and recovery of symptoms Figure. No caption available. Design and method: 60 patients admitted to Cukurova University Faculty of Medicine, Nephrology and Endocrinology Out Patient Clinics between 2010–2012 who had been diagnosed peripheric polyneuropathy associated with Diabetes Mellitus II-I Stage IV-V Chronic Kidney Disease and Primary Hypertension were included in this study. Disease related symptoms, medication usings, disease and neuropathy duration time were recorded. General physical examination was performed and routine laboratory tests, vitamin B12 and folate levels were asked in all patients. Before and after the treatment of Transcutaneous Electrical Nerve Stimulation (TENS) therapy. International scalas such as VAS (visual analog scala), LANNS (Leeds assesment of neuropathic symptoms and signs pain scale) and NHP (Nottingham health protocol) were performed and recorded. Transcutaneous Electrical Nerve Stimulation (TENS) therapy was applied to the patients 30 minutes daily for 3 weeks by physiotherapists in Departmant of Physical Therapy of Cukurova University. Results: Significant recovery were assessed in symptoms, in patients' life quality plus some decriments in systolic and diastolic blood pressures before and after therapy by using continiously blood pressure recorders and using parameters includings VAS, LANNS and NHP scalas. Conclusions: In our study, the symptoms of painfull polyneuropathy patients are improved withTranscutaneous Electrical Nerve Stimulation (TENS) therapy. Besides, there were significant improvement in symptoms and life quality of patients. Transcutaneous Electrical Nerve Stimulation (TENS) therapy is a valuable alternative therapy to drug theraphy in patients. We believe every such patients must have the right to use this very advanced technologically developped treatment modality. This is a sine qua non medical approach modality.